The feasibility of using glass facades for buildings in the State of Kuwait: جدوى استخدام الواجهات الزجاجية للمباني في دولة الكويت - Tariq Ibrahim Muhammad Al-Nukhailan (Journal of engineering sciences and information technology, 2022)
Recently, some press articles and opinions have come out that talk about aesthetic problems of glass facades. These problems are summed up in the excessive glare of these facades, raising the temperature in the external areas, and the effect of these facades by dust and storms that pass through the State of Kuwait, leaving a bad impact on them that loses their aesthetic value. I favored this research paper. To determine the extent to which these facades are suitable for the Kuwaiti climate, as there are towers with high-rise glass facades that occupy international ranks in terms of the elegance of the design and the aesthetics of the building. In the research, I wondered whether the process of transferring the use of these facades to our country was carried out without studying the climatic conditions of these countries. Or are there design errors in transportation, or is it a change in the climate, or are these facades suitable for the hot climate with some modifications to suit the climate? And I noticed through the research that most of the research tended to study the modern uses of facade glass in terms of providing comfort to the user and reducing energy. Through its content, the research dealt with a case study of some existing models of towers with glass facades in Kuwait, and conducting analyzes of them and studying the research related to them.